Spectrophotometric Determination of Metoclopramide in Some Pharmaceutical Preparation via Oxidative Coupling Reaction - Nief Ahmad; Najla Ali (College of Education for Pure Sciences, 2006)
the oxidation of promethazine by sodium hypochlorite and the coupling of the resulting product with metoclopraide in acetic acid medium to form a blue product with maximum absorption at 596 nm. Beer's law is obeyed over the concentration range of (3-30) gml,with molar absorptivity of 1.1104 L.mol-1.A relative standard deviation of the method was less than 1.2% and accuacy was 99.6% The optimum conditions for all colour development are described and the proposed method has been successfully applied for the determination of metoclopramide in pure durg and pharmaceutical formulation.The common excipients and additives did not interfere in this method. A simple spectrophotometric method for the determination of metoclopramide in a pure form and in dosage forms pharmaceutical preparations has been developed. The proposed method is based on